Evaluation and mapping of building overheating risk and air conditioning use due to the urban heat island effect. (November 2020) - Hwang, Ruey-Lung; Lin, Tzu-Ping; Lin, Feng-Yi
Abstract: Differences in urban context can lead to distinct local microclimates. The data provided by a single weather station are insufficient for evaluating residential thermal conditions and the air conditioning energy consumption of microscale areas throughout cities. The purpose of this study was to quantify the urban heat island (UHI) effect on air conditioning energy consumption and overheating risk in buildings. This study generated localized microclimate files of microscale areas from their urban contexts. A common three-story townhouse in Tainan City, Taiwan, was used as an example. EnergyPlus was used to simulate and analyze the effect of microclimate on residential overheating risk and air conditioning energy consumption citywide. Tainan was divided into 1496 microscale areas, and the analysis results indicated that dwellings in downtown and suburban areas faced an overheating risk for 3–5 months and exhibited a natural ventilation potential of 43%–47% from May to October. Furthermore, the air conditioning energy consumption of 60% of these microscale areas was 14.5–21.5 kWh/m 2, with 8% exceeding 21.5 kWh/m 2 . By contrast, the natural ventilation potential of dwellings in the countryside and peripheral areas was 63%–72%, and air conditioning energy consumption was ≤11.0 kWh/m 2 . These results highlight the importance of using localized microclimate files for evaluating building energy performance in urban areas. Highlights: Innovative dual AC energy and thermal risk evaluation based on UHI. EnergyPlus simulation with GIS-based microclimate data integration. 63% heat risk hours in the hottest area, compared to 23% in countryside. Downtown buildings consume additional 10.5 kWh/m 2 than countryside in summer.